On Australia’s Cyber and Critical Technology International Engagement Strategy Towards 6G: How Australia may become a leader in Cyberspace - Soldani, David (Journal of Telecommunications and the Digital Economy, 2020)
In response to the call by the Australian Department of Foreign Affairs and Trade for submissions on the development of Australia’s Cyber and Critical Technology International Engagement Strategy, this paper reviews the most critical technologies; related risks and opportunities; best practices, policies and security frameworks in other countries; relevant government, industry, civil society and academia cooperation initiatives; and proposes how Australia may became a leader in the global Cyberspace. To realise this vision, Australia should play a major role among selected international organizations; support the continuous evolution of critical technologies; adopt a proper technology security assurance scheme; and enforce a certification and accreditation process – against a predetermined set of appropriate security standards and policies – for security authorisation in Australia. This could be achieved with the formulation and implementation of an Australia’s defence-in-depth strategy, augmented by a Zero-Trust model, which enhances security for untrusted domains, and within trusted domains, and meets the baseline requirements of cyber security for the Internet of Things.